DESIGN AND DEVELOPMENT OF MEDICAL RECORD APPLICATION IN BULAN SABIT MERAH INDONESIA CLINIC SURABAYA BRANCH - teja, arya; ., Sulistiowati; Lemantara, Julianto (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2018)
Mojo BSMI Clinic is a healthcare service based on community, prime service, affordable price and quality. The problem is when patient’s health card is lost, the clinic staff will search the patient’s medical record before creating a new health card. The clinic staff is in difficult if medical record is lost or the document of medical record is not thoroughly searched, patient is considered has no medical record even though they have been treated in clinic before. But the patient still will get their new medical record by staff, it makes accumulation on medical record document, and staff does not know whether they are new patient or not.As the problem described, the solution is to create an application for medical record that has several function such data searching, medical record, and create a monthly report. On medical record, diagnose classification for disease using ICD 9 and 10.The test result and evaluation has shown that Design of Medical Record Application at BSMI Clinic Surabaya able to generate medical record information, the patient visits, income report and top ten disease report. And also the application can accelerate data searching process and medical report that helps the doctor at BSMI Clinic.